Indo-Pacific Security Concept: Format and Constraints - Syaiful Anwar (The Republic of Indonesia Defense University, 2015)
Indo-Pacific Security Concept is a new initiative, proposed by several parties, linking the regions within the eastern part of Indian Ocean and the western part of Pacific Ocean. There is an expectation that the new architecture can contribute to facilitate communication among members to maintain a peaceful and stable region. Based on the nature of the region, the new architecture can also facilitate the practical cooperation for maritime security. However, several parties also concern that various challenges will emerge in building this new architecture. Indonesia, located at the centre of this region, can play an important role in accomodating the interests of the parties involved.